2017
DOI: 10.1021/acs.jpca.7b08614
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Study of Thermodynamics of the Reaction of Titania and Water at High Temperatures

Abstract: Gaseous titanium hydroxide and oxyhydroxide species were studied with quantum chemical methods. The results are used in conjunction with an experimental transpiration study of titanium dioxide (TiO) in water vapor-containing environments at elevated temperatures to provide a thermodynamic description of the Ti(OH)(g) and TiO(OH)(g) species. The geometry and harmonic vibrational frequencies of these species were computed using the coupled-cluster singles and doubles method with a perturbative correction for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 33 publications
4
33
1
Order By: Relevance
“…Furthermore, only one experiment (preoxidized sample) directly lends itself to this discussion since the other tests exhibit only weight gains. Volatility rates of oxides can be calculated from the equilibrium vapor pressure of the hydroxide species and the gas conditions in the burner using the mass transport equation for laminar (or turbulent) flow in a moving boundary layer [32][33][34]1,4]. Using published values for the thermodynamic energy of compound formation, these pressures and fluxes were calculated (i.e., Jacobson) and listed in Table 3 [32, 37,38].…”
Section: Volatility Rates and Cubic-linear Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, only one experiment (preoxidized sample) directly lends itself to this discussion since the other tests exhibit only weight gains. Volatility rates of oxides can be calculated from the equilibrium vapor pressure of the hydroxide species and the gas conditions in the burner using the mass transport equation for laminar (or turbulent) flow in a moving boundary layer [32][33][34]1,4]. Using published values for the thermodynamic energy of compound formation, these pressures and fluxes were calculated (i.e., Jacobson) and listed in Table 3 [32, 37,38].…”
Section: Volatility Rates and Cubic-linear Behaviormentioning
confidence: 99%
“…Some uncertainty has been raised regarding the thermodynamic data used for TiO(OH) 2 due in part to analysis difficulties for the low yields of condensed species in the transpiration experiment [4,32]. Thus it appears that experimental rates are higher than those predicted for Ti-oxide losses in water vapor.…”
Section: Volatility Rates and Cubic-linear Behaviormentioning
confidence: 99%
“…Weight 111 , however they are significantly higher than the flux calculated for these test conditions using thermodynamic data of Nguyen et al 110 .…”
Section: Background: Volatility Of Sio2 Tio2 and Y2o3contrasting
confidence: 52%
“…A transpiration study by Nguyen et al 110 concluded that TiO2 (rutile) reacts with water vapor by Equation (3.1),…”
Section: Background: Volatility Of Sio2 Tio2 and Y2o3mentioning
confidence: 99%
See 1 more Smart Citation